UAV-measured vertical ozone profile (0–1000 m) and model-estimated regulation effect on the western coast of Japan in autumn 2023 - Syuichi Itahashi (Science of Remote Sensing)
Tropospheric ozone (O3) remains a severe air pollution problem in East Asia. In this study, we used an uncrewed aerial vehicle (UAV) to measure the long-range transported O3 at Goto Island, the westernmost place in Japan, on 3 and 4 October 2023. The O3 vertical profile was measured from the surface to 1000 m 10 times. The surface O3 concentration showed a typical diurnal variation; however, the UAV measurement clarified that the O3 concentration was lower at the surface and increased toward 1000 m in the morning, whereas the O3 concentration was constant from the surface to 1000 m from noon to afternoon. The air quality model was validated comprehensively using UAV measurements from the surface to 1000 m. Although the model generally captured the vertical O3 profile, it had difficulty reproducing the lower O3 at the surface level in the morning, indicating that further improvements are required. The O3 concentration at 1000 m showed smaller diurnal variation compared with the surface level. Furthermore, the effects of NOx emission reduction from China, the Republic of Korea, and Japan were estimated by the validated model. These estimations showed that their variability was related to the wind field through the campaign period. This study provides a research framework of integrating UAV measurements and models for long-range transported O3 in East Asia.